2021
DOI: 10.1071/py20297
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner knowledge of and engagement with telehealth-at-home medical abortion provision

Abstract: In Australia, there are many barriers to abortion, particularly for women living in regional, rural and remote areas. Telehealth provision of medical abortion is safe, effective and acceptable to patients and providers. In 2015, Marie Stopes Australia (MSA) launched an at-home telehealth model for medical abortion to which GPs could refer. Between April and November of 2017, we interviewed 20 GPs who referred patients to MSA’s telehealth-at-home abortion service to better understand their experiences and persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Other studies in rural Australia have focused on women's experiences of abortion services once reached and the perspective of service providers about the delivery of care, including provision via telehealth (Doran and Hornibrook 2016;Dawson et al 2017;Hulme-Chambers et al 2018;Fix et al 2020;Ireland et al 2020;Cashman et al 2021;Mazza et al 2021;Malatzky and Hulme 2022). These studies have also found results similar to ours, that multiple systemic challenges exist for rural women when accessing services.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Other studies in rural Australia have focused on women's experiences of abortion services once reached and the perspective of service providers about the delivery of care, including provision via telehealth (Doran and Hornibrook 2016;Dawson et al 2017;Hulme-Chambers et al 2018;Fix et al 2020;Ireland et al 2020;Cashman et al 2021;Mazza et al 2021;Malatzky and Hulme 2022). These studies have also found results similar to ours, that multiple systemic challenges exist for rural women when accessing services.…”
Section: Discussionsupporting
confidence: 79%
“…In a study examining access, equity and costs of induced abortion in Australia, the strongest predictor of late presentation (beyond 9 weeks) was living ≥4 h from the abortion clinic (Shankar et al 2017). Access barriers are well documented in relation to abortion care in Australia (Dawson et al 2017;Hulme-Chambers et al 2018;Fix et al 2020;Ireland et al 2020;Cashman et al 2021;Mazza et al 2021); however, little is known about the role of local generalist primary care providers in rural settings as the first point of contact for women seeking advice or services for unintended pregnancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This innovative approach to consumer and health professional engagement will ensure that the ORIENT intervention addresses consumer needs, is evidence-based, feasible, sustainable and offers the best chance of success. Through our extensive research, we have gathered patient and provider experience5 43–46 and systematically reviewed the literature 21. We have been able to understand the lived experience and patient journeys of consumers through audits of existing nurse-led models of care in community health and family planning settings22 and a large RCT of online education and rapid referral to LARC insertion 36.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…Several articles deal with the importance of knowledge and attitudes in influencing access to care and outcomes for people, as well as reporting on interventions to address these. Mazza et al (2021) report on a qualitative study of general practitioners' understanding and engagement with telehealth-at-home abortion providers. Parker and colleagues (2021) investigate the attitudes of health professionals to an online support tool for carers of people at the end of their lives.…”
mentioning
confidence: 99%